General aspects of tomato culture and phosphate fertilization: a systematic review - Lopes Sobrinho, Oswaldo Palma; Santos, Leonardo Nazário Silva dos; Soares, Frederico Antonio Loureiro; Cunha, Fernando Nobre; Vidal, Vitor Marques; Teixeira, Marconi Batista (Comunicata Scientiae, 2022)
O tomate ( Solanum lycopersicum L.) is at the top of the ranking among the most consumed vegetables in the world and can be grown in open fields and, mainly, in agricultural greenhouses. Therefore, the adjustment of phosphate fertilizer in its cultivation can influence higher yields, fruit quality and nutritional status. In view of the socioeconomic importance of tomatoes due to their antioxidant properties, bioactive compounds, carbohydrates, proteins, minerals and the guarantee of jobs for farmers, this literature review seeks to present a study that provides technical and scientific data on general and the important role of phosphate fertilization in tomato cultivation. The main focus of this study is justified by the absence of studies that analyze the general aspects and the responses of the tomato in function of the water deficit and doses and sources of phosphorus. Through the analysis of secondary data available in the literature related to the theme, there is a difficulty in adjusting the phosphate fertilizer according to the appropriate choice of doses and sources to be applied. Furthermore, as it is a vegetable sensitive to water deficit, fruit yield and quality can be influenced by the amount of water that is applied and the management of irrigation in combination with the correct amount of fertilizer.